RFID Tags Detectors Stability Analysis Under Delayed Schottky Diode’s Internal Elements in Time - Aluf, Ofer (Discoveries in Agriculture and Food Sciences, 2016)
In this article, we discuss the crucial subject of stability analysis of RFID tag detectors under Schottky diode’s internal time delay elements. The Schottky diode detector demodulates the signal and sends the data on to the digital circuit of the TAG; this is the so-called "wake up" signal. A simple RFID TAG receiver block diagram includes input antenna signal with series resistance, inductor (choke), Schottky diode, and output capacitor. Due to the Schottky parasitic delay, there is a stability issue in analyzing detector operation. We define τ1, τ2 as delays in time respectively for a Schottky equivalent circuit. We first consider those two delays in time that are not equal τ1≠τ2 then the other three cases τ1= τ & τ2=0, τ 2= τ & τ1=0, τ1= τ2= τ. The RFID receiver detector time delay equivalent circuit can be represent as delayed differential equations that depend on variable parameters and delays. The article illustrates certain observations, and analyzes local bifurcations of an appropriate arbitrary scalar delayed differential equation. All of that for optimization of an RFID receiver detector equivalent circuit parameters analysis to get the best performance.